Analisis Keamanan Infrastruktur Teknologi Informasi dalam Menghadapi Ancaman Cybersecurity - Omer Hoshmand, Mohammad; Ratnawati , Suci (Applied Information Technology and Computer Science (AICOMS), 2023)
In the ever-growing digital era, Information Technology (IT) infrastructure security has become an urgent need. Cybersecurity threats are increasingly complex and diverse, requiring organizations to adopt a proactive approach to protecting systems and data. This research aims to conduct an IT infrastructure security analysis and identify effective strategies in dealing with cyber security threats. The research method used is literature study, with a focus on the latest literature discussing cyber security, IT infrastructure and related technologies. The analysis was conducted to evaluate commonly used security frameworks and identify current trends, challenges and solutions in addressing cybersecurity threats. The research results show that successful IT infrastructure security requires a holistic approach that includes technical aspects, policies and human resource training. Regular software updates, implementation of advanced security technologies, and proactive monitoring can help reduce the risk of cyber threats. In addition, strict security policies and ongoing training for personnel are key to mitigating risks.